A Journey towards Improved Quality of Life of a Typist with Retinitis Pigmintosa - Malab Sana Balouch; Muhammad Shahbaz; Mohammad Moaz Balouch (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Abstract: Retinitis pigmentosa (RP) is a group of inherited rod-cone degenerative pathologies that present clinically with similar signs and symptoms. Common fundus findings include bone-spicule pigment formation, attenuated blood vessels in the posterior pole and waxy optic nerve pallor. Symptoms mostly start with progressive night blindness, mid-peripheral visual field defects, and eventual tunnel vision. A 42 year old male patient, typist by profession presented to our clinic with complaints of decreased vision and reduced dark adaptation affecting his quality of life a lot. On examination, he was diagnosed as an advanced case of retinitis pigmentosa bilaterally and there was bilateral posterior sub capsular cataract. His quality of life was assessed by using a simplified version of the VFQ-25 questionnaire. After successful cataract surgery and low vision rehabilitation his quality of life was reassessed by using same questionnaire. He had a much more positive outlook towards his eyesight. Our case report reviews the life changing personalized low vision rehabilitation of a typist with retinitis pigmentosa. Key words: retinitis pigmentosa, quality of life, low vision rehabilitation